Children in care in education: Who is entered for exams and who reaches critical thresholds of success at age 16?. (29th June 2021) - O'Higgins, Aoife; Luke, Nikki; Strand, Steve
Abstract : Being entered for exams and reaching key educational thresholds, for example 5 A* to C grades (including English and Mathematics) at GCSE, are important markers of participation and success in secondary education. However, little is known about the prevalence and make‐up of children in care reaching these thresholds. Using secondary data analysis, we compared the proportions of children in care, children 'in need' and children in the general population who achieved four key thresholds, including exam entry and 5 A* to C grades, including English and Mathematics. We then focused on children in care and examined factors that predicted exam entry and achieving 5 A* to C grades, including English and Mathematics. Children receiving social care interventions were less likely than children in the general population to be entered for exams or to reach important educational thresholds. For children in care, several socio‐demographic, care and educational factors predicted their likelihood of success. No children with an autistic spectrum disorder or who had ever been permanently excluded were recorded to have achieved 5 A* to C grades, including English and Mathematics. Children with poor attainment at Key Stage 2 were also at significant risk of not achieving this threshold. Practitioners and policymakers should consider the modifiable risk factors for poor educational performance and be aware of groups of children in care who are at significant risk of not achieving a minimum standard which could open doors for their future.